2014
DOI: 10.1002/esp.3562
|View full text |Cite
|
Sign up to set email alerts
|

Impact of reach geometry on stream channel sensitivity to extreme floods

Abstract: Predicting spatial and temporal variations in bank erosion due to extreme floods presents a long‐standing challenge in geomorphology. We develop two methodologies for rapid, regional‐scale assessments of stream reaches susceptible to channel widening. The first proposes that channel widening occurs when unit stream power exceeds a critical threshold (300 W/m2). The second is motivated by the observation that widening often occurs at channel bends. We introduce a new metric, the bend stress parameter, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 79 publications
0
54
0
1
Order By: Relevance
“…Therefore, in terms of hazard, documenting the type and magnitude of channel response is crucial in identifying controlling factors of such response and in developing tools to enable channel dynamic predictions. Recently, Buraas et al (2014) stated that there is still a general lack in the capability to predict where major geomorphic changes take place during an extreme flood event. In this respect, the regression models and other outcomes of this study can be used to predict the degree of channel widening and to support planning along river corridors through hazard mapping.…”
Section: Practical Implication For River Management and Risk Mitigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in terms of hazard, documenting the type and magnitude of channel response is crucial in identifying controlling factors of such response and in developing tools to enable channel dynamic predictions. Recently, Buraas et al (2014) stated that there is still a general lack in the capability to predict where major geomorphic changes take place during an extreme flood event. In this respect, the regression models and other outcomes of this study can be used to predict the degree of channel widening and to support planning along river corridors through hazard mapping.…”
Section: Practical Implication For River Management and Risk Mitigationmentioning
confidence: 99%
“…Some works have confirmed that hydraulic forces may not be sufficient to explain geomorphic effects (e.g., Heritage et al, 2004;Nardi and Rinaldi, 2015), and consequently, attempts have been made to include other factors. For instance, human interventions and structures have been considered by Langhammer (2010); bedload supply and pre-flood channel planform by Dean and Schmidt (2013); lateral confinement by Thompson and Croke (2013); a bend stress parameter by Buraas et al (2014).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of lateral instability, Buraas et al [184] made some headway by demonstrating how widening and large scale geomorphic change relate to crossing a threshold specific stream power (for the 2-year flow) of 300 W·m −2 during flood events, which facilitated a regional assessment of reaches susceptible to bank erosion. Conceivably then, it would be possible to estimate the proportion of AGE that might be associated with large scale bank retreat and map susceptible reaches.…”
Section: Discussionmentioning
confidence: 99%
“…The employment of flow duration curves in the energy auditing methodology intrinsic to Equation (7) represents a marked difference with other approaches that use single, representative discharges derived from either regional expressions (e.g., [2,116,120,184]) or broad hydrological models (e.g., [118,123,125]). Indeed, Biron et al [126] considered the weakest area in most stream power mapping approaches to be the single, regional-based estimation of bankfull discharge.…”
Section: Channel Dischargementioning
confidence: 99%
“…Urbanization can increase flood velocity and thus decrease the time to flood peak, reducing the time a community has to evacuate homes. In addition, urbanization and channel confinement have been shown to increase stream power and dangerous fluvial erosion damages that lead to bank failure (Kline and Cahoon 2010;Buraas 2014). Fluvial erosion studies required to assess potential bank failure also depend on streamflow measurements unavailable in this area of study.…”
Section: Study Limitationsmentioning
confidence: 98%